A Case of Mosaic Down Syndrome - Habib, Saequa (Bangladesh Journal of Pathology, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Cytogenetic analysis in 44 clinically suspected cases of Down syndrome (DS) was carried out using conventional Giemsa-trypsin-banding technique. Among them 43 cases were cytogenetically proved as DS. Forty-two individuals (97.7%) exhibited pure trisomy 21. The remaining child was a seven years old boy, the second-born of nonconsanguineous parents and had 46/47XY, +21 mosaicism. He also possessed most of the phenotypic characteristics of the classical trisomy 21. Keywords: Cytogenetic analysis, Down syndrome, syndrome. doi: 10.3329/bjpath.v24i1.2880 Bangladesh J Pathol 24 (1) : 28-30